Bacteriologica acteriological examinations of ducklings, duck's eggs, feed, and rice bran collected from Alibio market, South Kalimantan - Istiana .; Suryana . (Jurnal Ilmu Ternak dan Veteriner, 1997)
Bakteriological examinations of samples consisted of ducklings, duck's eggs feed and rice bran collected from Alabio market, South Kalimantan were conducted in the laboratory during the year 1992 and 1993 . Result of the examinations showed that 22 isolates of Salmonella Hadar, were isolated from 180 internal organ of ducklings (12 .2%), while 1 isolate of Salmonella Typhimurium (0 .5%), and 1 isolate of Salmonella Virchow (0 .5%) was isolated respectively from 180 duck's eggs. Besides, other bacteria were also isolated namely Escherichia coli, Pseudomonas sp., Klebsiella sp ., Citrobacter sp . Enterobacter sp, Proteus sp., and Serratia sp . No pathogenic bacteria were isolated from feed as well as from rice bran .   Keywords : Alabio ducklings, duck's eggs, feed, rice bran, Salmonella spp ., South Kalimantan